KEBIJAKAN PERTAHANAN KEAMANAN KOREA SELATAN DALAM MENGHADAPI ANCAMAN NUKLIR KOREA UTARA ANTARA TAHUN 2002-2012 - Thalib, Haikal Hasan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACT North Korea's nuclear threat is one of the serious problems currently faced South Korea as North Korea's closest neighboring countries. The presence of a dark past history involved raises concerns about the nuclear threat from North Korea is likely to threaten the region and threaten the safety of its citizens. North Korea's nuclear threat is what makes the South Korean government did the various policies related to the security of South Korea's defense in the form of co-operation between the State, to make peace efforts against North Korea. Keywords:Threats, Nuclear North Korea, South Korea's Defense and Security Policy